Analysis of factors for increasing e-commerce adoption with intervening attitude variables for JABOTABEK MSMEs - Idhi Heru Supriyadi; Sri Lestari Prasilowati; Suyanto Suyanto (Faculty of Economics and Business Mulawarman University, 2023)
This study aims to analyze the effect of time-saving, cost-effective, security assurance, easy to use, product quality (compatibility) on e-commerce adoption with attitude as a mediation between ease of use and product quality (compatibility) with e-commerce adoption in MSMEs in the region. Jakarta, Bogor, Tangerang, Bekasi. The population in this study is the owners of MSMEs engaged in the food business in the areas of Jakarta, Bogor, Tangerang, Bekasi. Number of samples was taken based on Hair et al (2019) so that 140 respondents were obtained. The data processing method used in this study is a descriptive quantitative research with a causal approach. Data analysis using Structural Equation Model (SEM) with Smart PLS (Partial Least Square) 3.0. The independent variables in this study is time-saving (X1), cost-effective (X2), security assurance (X3), easy to use (X4), and product quality (compatibility) (X5). The moderating variable in this study is attitude (Z). The dependent variable in this study is e-commerce adoption (Y). The results showed that there was a positive and significant effect of saving time, saving costs, guaranteeing security, easy to use, product quality (compatibility) on e-commerce adoption. Variables easy to use and product quality (compatibility) have a significant positive effect on attitude. Attitude variable has a significant positive effect on e-commerce adoption.